Penerapan Model Behavioristik dalam Pembelajaran PAI Berbasis Teknologi - Syakur, Albert Taqy Asy; Nurkhasanah, Mita; Haryadi, Yaniz Naura Naviana; Khuriyah, Khuriyah (TSAQOFAH, 2025)
The application of the behavioristic model in technology-based Islamic Religious Education (PAI) learning focuses on changing student behavior through appropriate stimulation. Behaviorism as a learning theory emphasizes that human behavior can be manipulated and learned through interaction with the environment. In the PAI context, the use of technology functions as a tool to strengthen the learning process, increase understanding, and shape the character of students. Through the literature review method, this article discusses the contribution of behaviorist theory in creating effective learning designs, as well as the importance of technology integration to achieve more holistic educational goals. The results show that the behavioristic learning model can increase students' motivation and responses, as well as facilitate positive attitude changes.